Prawne umocowanie kształcenia dualnego w Krajowej Szkole Administracji Publicznej - Gofron, Paweł (PRAWO i WIĘŹ, 2025)
This paper outlines the concept and rules of dual-path training at the National School of Public Administration. The main objective of this paper is to highlight the legal basis for this method of developing competence. In this context, the key regulations resulting from the amendment to the Act on the National School of Public Administration are cited and discussed. The provisions of the School’s Charter relating directly to dual-path training were then analysed.